Trend of risk and correlates of under-five child undernutrition in Bangladesh: an analysis based on Bangladesh Demographic and Health Survey data, 2007–2017/2018 - Md Tahidur Rahman; Md Jahangir Alam; Noyon Ahmed; Dulal Chandra Roy; Papia Sultana (BMJ Open, 2023)
Objectives The objectives of this study are to identify the trend of undernutrition risk among under-five children (U5C) in Bangladesh and the trend of its correlates.Design Multiple cross-sectional data sets from different time points were used.Setting Nationally representative Bangladesh Demographic and Health Surveys (BDHSs) were conducted in 2007, 2011, 2014 and 2017/2018.Participants In the BDHSs, the sample sizes for ever-married women (age: 15–49 years) were 5300 in 2007, 7647 in 2011, 6965 in 2014 and 7902 in 2017/2018.Outcomes Extant indicators of undernutrition (stunted, wasted and underweight) have been considered as the outcome variables.Materials and methods Descriptive statistics, bivariate analysis and factor loadings from factor analysis have been used to determine the prevalence of undernutrition over the years and find the trend of risk and its correlates.Results Risks of stunting among the U5C were 41.70%, 40.67%, 36.57% and 31.14%; that of wasting were 16.94%, 15.48%, 14.43% and 8.44%; and that of underweight were 39.79%, 35.80%, 32.45% and 22.46% in 2007, 2011, 2014 and 2017/2018, respectively. From the factor analysis, it has been found that the top five potential correlates of undernutrition are the wealth index, the education of the father and mother, the frequency of antenatal visits during pregnancy, the father’s occupation and/or the type of place of residence in the last four consecutive surveys.Conclusion This study helps us gain a better understanding of the impact of the top correlates on child undernutrition. To accelerate the reduction of child undernutrition more by 2030, Government and non-government organisations should focus on improving education and household income-generating activities among poor households and raising awareness among women about the importance of receiving antenatal care during pregnancy.